Multi-Functional Land Use Is Not Self-Evident for European Farmers: A Critical Review - Schröder, Jaap J.; Ten Berge, Hein F. M.; Bampa, Francesca; Creamer, Rachel E.; Giraldez-Cervera, Juan V.; Henriksen, Christian B.; Olesen, Jørgen E.; Rutgers, Michiel; Sandén, Taru; Spiegel, Heide (Frontiers in Environmental Science, 2020)
Soils perform more functions than primary productivity. Examples of these functions are the recycling of nutrients, the regulation and purification of water, the regulation of the climate, and supporting biodiversity. These abilities are generally referred to as the soil quality. Soil management that favours primary productivity may have positive and negative impacts on the other functions, and vice versa, depending on soil and climatic conditions. All these functions are under pressure, particularly in intensive agriculture. In the absence of mandatory regulations, most European farmers give limited attention to other functions than primary productivity in spite of pleas by scientists, society and policy makers to acknowledge the ecosystem services provided by soils. The present paper analyses the underlying causes of this limited attention for the multi-functionality of soils by farmers. It is concluded that their focus on primary productivity may stem from 1) insufficient visible proof for soil degradation and benefits of preventive measures over curative measures, 2) limited awareness or conviction of long-term synergies, 3) insufficient remuneration of ecosystem services by society or compensation of yield penalties in favour of these services, 4) lacking trustworthy knowledge about and support for multi-functional soil management, and 5) absence of incentives and regulations on soil management and their enforcement. All these shortcomings need to be addressed by advisors, scientists and policy makers, whilst acknowledging the need for underpinning and differentiation of incentives and regulations.